Monks relax sibling competition over parental resources in Tibetan populations. (21st September 2022) - Zhou, Liqiong; Ge, Erhao; Micheletti, Alberto J C; Chen, Yuan; Du, Juan; Mace, Ruth
Abstract: Why parents in some societies induce some of their sons to become religious celibates is an evolutionary puzzle. Some have speculated that this might be associated with brother competition for family resources. However, the behavioral ecology of monks and the possible links with competition between brothers remain unexplored. Here, we use demographic data from Amdo Tibetan agropastoralists in western China to evaluate what factors determine the probability of becoming a monk and explore the possible association between wealth and having a monk brother. We found that boys with at least one older brother are more likely to become celibate monks. Patrilocal heads of household, who inherit parental property, are more likely to be first-born sons, whereas men who marry uxorilocally, that is they move to their wife's household, are generally second- or later-born sons. Moreover, we find that men with at least one monk brother are wealthier than men who only have non-celibate brothers. Together, these results suggest that sending a son to the monastery is a way for parents to decrease competition between brothers over family resources. Harsh and resource-limited environments, like the one we consider, can lead to the emergence of communal households, including polyandrous families, which used to be common in Tibetan areas. Directing one son to become a religious celibate offers a potentially effective solution to brother competition in our population. Abstract : We find that parents send a son to the monastery to decrease brother competition over resources in a Tibetan population. Men with monk brothers are wealthier than men with non-celibate brothers. Monks are generally second-born sons, while first-born sons tend to inherit the parental household. Non-inheritors may also move to their wife's household or migrate elsewhere. Religious celibacy and new economic opportunities act together to limit the negative effects of brother competition.